The Impact of Digital Payment Systems on the Income of Micro, Small, and Medium Enterprises in Aceh Barat Regency (Case Study of Johan Pahlawan District) - Muarif, Syamsul; Syahril, Syahril; Risma, Okta Rabiana; Ariani, Dian; Suhendra, Noval (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of digital technology has driven the transformation of payment system across various economic sectors, including micro, small, and medium enterprises (MSMEs). However, the adoption of Digital Payment in west Aceh Regency, particularly in Johan Pahlawan District, remains limited despite its potential to enhance transaction efficiency and business income. The purpose of this research is to examine how Digital Payment adoption impacts the income of MSMEs in Johan Pahlawan District. Employing a quantitative methodology, primary data were gathered via questionnaires distributed to 100 MSME operators who utilize Digital Payment systems. Data analysis was conducted using simple linear regression, revealing that the implementation of Digital Payment exerts a significant and positive influence on MSME revenues These findings suggest that increased utilization of Digital Payment systems can support income growth among MSMEs, although its contribution is not yet dominant. Therefore, Digital Payment can be concluded as one of the supporting factors in improving MSMEs income performance at the local level.